1992
DOI: 10.1007/bf03258363
|View full text |Cite
|
Sign up to set email alerts
|

S-Adenosyl-L-Methionine Prevents Intracellular Glutathione Depletion by GSH-Depleting Drugs in Rat and Human Hepatocytes

Abstract: SummaryThis study examines the ability of externally added S-adenosyl-L-methionine (SAMe) to act as a precursor of intracellular glutathione (GSH) and to prevent the GSH depletion induced by paracetamol, opiates and ethanol in rat and human hepatocytes.Incubation of rat or human hepatocytes with SAMe 100 I'moljL as the only sulphur source in the medium resulted in a time-dependent elevation of intracellular GSH. Pretreatment of hepatocytes with SAMe resulted in a significant decrease in the cytotoxicity produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…We have already mentioned that the main metabolic functions ascribed to S-MAe, among which are restoration and increases in hepatic GSH reserves, are worth noting. During hepatic oxidative stress, a decrease in the S-AMe-synthetase activity is usual; this leads to the oxidation of the SH groups in the enzyme [Pisi and Marchesini, 1990;Jover et al, 1992]. Such a phenomenon creates the following vicious cycle: low concentrations of GSHoxidative stressincrease in the inhibition of S-AMe-synthetase marked reduction in GSH reserves.…”
Section: Discussionmentioning
confidence: 99%
“…We have already mentioned that the main metabolic functions ascribed to S-MAe, among which are restoration and increases in hepatic GSH reserves, are worth noting. During hepatic oxidative stress, a decrease in the S-AMe-synthetase activity is usual; this leads to the oxidation of the SH groups in the enzyme [Pisi and Marchesini, 1990;Jover et al, 1992]. Such a phenomenon creates the following vicious cycle: low concentrations of GSHoxidative stressincrease in the inhibition of S-AMe-synthetase marked reduction in GSH reserves.…”
Section: Discussionmentioning
confidence: 99%
“…The protective effect of S-adenosylmethionine against menadione cytotoxicity may be explained by its ability to prevent glutathione depletion (Friedel et al, 1989;Jover et al, 1992). Interestingly, in stationary cultures the presence of or the pretreatment with S-adenosylmethionine resulted in a shift of the cytotoxic concentrations for menadione to only slightly higher values.…”
Section: Discussionmentioning
confidence: 99%
“…S-adenosylmethionine (SAMe) is a thiolic compound that plays an important role in transmethylation and transsulphuration reactions. SAMe has been reported to prevent and reverse the cholestasis and hepatotoxicity associated with several drugs and chemical compounds, either by normalizing membrane fluidity through methylation of membrane phospholipids or by maintaining the hepatic pool of glutathione (Corrales et al, 1992;Jover et al, 1992). We have previously shown that SAMe cotreatment protects against glutathione depletion, changes in hepatocyte membrane fluidity and composition, and abnormalities in biliary bile acid, lipid and protein secretion induced by CyA (Fernández et al, 1995;Galán et al, 1995).…”
Section: Introductionmentioning
confidence: 99%